2022
DOI: 10.1021/acs.nanolett.1c04968
|View full text |Cite
|
Sign up to set email alerts
|

Aminophenol-Decorated Gold Nanoparticles for Curing Bacterial Infections

Abstract: Nanomaterials usually kill bacteria via multiple mechanisms which are not explicit to the same degree as those of conventional antibiotics. This situation may hinder the development of novel nanoscale antibiotics. Here, we present aminophenol (AP) to modify gold nanoparticles (AP_Au NPs) which show a broad antibacterial spectrum and potent antibacterial effects against multidrug-resistant (MDR) bacteria with clear antibacterial mechanisms. AP_Au NPs can not only damage bacterial cell walls but also bind to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Aminoglycoside antibiotics work primarily by inhibiting the synthesis of bacterial proteins, which are mainly used for systemic infections caused by sensitive aerobic Gram-negative bacilli in clinical practice [ 80 ]. Inspired by the structural characteristics of aminoglycoside antibiotics, Wang and coworkers designed aminophenol modify Au nanoparticles (AP_Au NPs) with broad antibacterial spectrum against multidrug-resistant bacteria [ 81 ]. AP_Au NPs with hydroxyl groups bind to the 16S rRNA molecules of bacteria by forming hydrogen bonds to block bacterial protein synthesis, ultimately causing bacterial death ( Figure 5 ).…”
Section: Planktonic Bacteriamentioning
confidence: 99%
“…Aminoglycoside antibiotics work primarily by inhibiting the synthesis of bacterial proteins, which are mainly used for systemic infections caused by sensitive aerobic Gram-negative bacilli in clinical practice [ 80 ]. Inspired by the structural characteristics of aminoglycoside antibiotics, Wang and coworkers designed aminophenol modify Au nanoparticles (AP_Au NPs) with broad antibacterial spectrum against multidrug-resistant bacteria [ 81 ]. AP_Au NPs with hydroxyl groups bind to the 16S rRNA molecules of bacteria by forming hydrogen bonds to block bacterial protein synthesis, ultimately causing bacterial death ( Figure 5 ).…”
Section: Planktonic Bacteriamentioning
confidence: 99%
“…Drug-resistant bacterial infections pose a serious threat to human health. 1,2 The World Health Organization (WHO) reported that there would be more than 10 million people dying because of antibiotic-resistant infections by 2050, and the cost of healthcare would reach $100 trillion every year. 3 Moreover, more than 50% of Staphylococcus aureus (S. aureus) strains isolated from hospital-acquired and communityacquired infections are methicillin resistant, 4 and some of them are even resistant to last-resort antibiotics vancomycin and linezolid.…”
Section: Introductionmentioning
confidence: 99%
“…5 Targeted drug delivery using Au NPs has been tested in tumors, the liver, lung, and inhalation. [6][7][8][9] Recent research showed specific modified Au NPs have antibacterial activity 10 antioxidant activities, 11 and detect SARS-CoV-2. 12 Although relatively low toxicity has been reported on Au NPs, most researchers agree that exposure to nano-scale materials can lead to chronic toxicity, which may be due to the responses at the gene and protein level.…”
Section: Introductionmentioning
confidence: 99%